THE INFLUENCE OF WORK DISCIPLINE ON EMPLOYEE EMPLOYMENT BUSINESS DIVISION AT SMK PGRI 2 BELITANG OGAN KOMERING ULU TIMUR - Mardani Mardani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
The purpose of this study is to determine the magnitude of the influence of work discipline on the performance of employees in the administration section of SMK PGRI 2 BELITANG OKU Timur. The conclusion obtained is r = 0.73 which has been consulted with a conservative standard, it is located between 0.600- 0.799, which means it belongs to a strong correlation or influence between work discipline and the performance of administrative staff at SMK PGRI 2 Belitang OKU Timur and after being held Hypothesis test is known t count = 2.99 and t table obtained 1.860 The suggestion that can be given is that the agency must provide motivation to its employees so that employees are always disciplined in their work. Key words: work discipline, performance